2004
DOI: 10.3748/wjg.v10.i10.1508
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at cholesterol 7α-hydroxylase, apolipoproteins B and E and low density lipoprotein receptor genes in patients with gallbladder stone disease

Abstract: AIM: To investigate the relationship between gallbladder stone disease (GSD) and single nucleotide polymorphisms of cholesterol 7α-hydroxylase (CYP7A) gene promoter, apolipoprotein (APO) B gene exon 26, APOE gene exon 4 or microsatellite polymorphism of low density lipoprotein receptor (LDLR) gene exon 18. METHODS:Genotypes of CYP7A, APOB, APOE and LDLR genes were determined in 105 patients with GSD diagnosed by B-mode ultrasonography and 274 control subjects. Serum lipids were analyzed with HITACHI 7060 autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 38 publications
1
27
2
1
Order By: Relevance
“…Most studies concerning genetic variations in the CYP7A1 gene have focused on an A-C SNP in the promoter region, which is at position À278 from the translation initiation codon or position À204 from the transcriptional start site. The results appear to be conflicting as to whether this polymorphism is significantly associated with, for example, plasma lipid levels, 7-9 risk of arteriosclerosis 10 and gallstone disease [11][12][13] in adults and children from Caucasian and Asian populations. Some intervention trials have suggested that the polymorphism has an important role in the metabolism of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies concerning genetic variations in the CYP7A1 gene have focused on an A-C SNP in the promoter region, which is at position À278 from the translation initiation codon or position À204 from the transcriptional start site. The results appear to be conflicting as to whether this polymorphism is significantly associated with, for example, plasma lipid levels, 7-9 risk of arteriosclerosis 10 and gallstone disease [11][12][13] in adults and children from Caucasian and Asian populations. Some intervention trials have suggested that the polymorphism has an important role in the metabolism of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Recent human genetic studies have indicated that genes involved in bile salt balance, including cholecystokinin A receptor and CYP7A1, are susceptibility genes for gallstone disease (Miyasaka et al, 2002;Jiang et al, 2004). Compared to the Gly388 variant, the Gly388Arg (G-388R) variation in the transmembrane domain (exon 9) of the FGFR4 protein results in FGFR4 stabilization and increasing phosphorylation after ligand binding (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hereditary contribution of cholesterol 7α-hydroxylase and apolipoprotein E and B genes to gallstone formation were reported. 84,85) In addition, as described above, based on the fact that hypersecretion of cholesterol into bile has been identified as the primary pathogenic event in gallstone formation, 86) gene mutations and single nucleotide polymorphisms (SNPs) of ABCG5 and ABCG8 have attracted considerable attention. To date, several SNPs of ABCG5 and ABCG8 were reported to be associated with cholesterol gallstone disease.…”
Section: Fig 4 Drug Interaction Between Ezetimibe and Warfarinmentioning
confidence: 99%